ALTERNATIVE RETURN FOR STATE LOSSES IN CRIME CASES - Vivi Arfiani Siregar; Feni Puspitasari (International Journal of Multidisciplinary Research and Literature, 2023)
State financial losses can take many forms, including the expenditure of state assets that exceed what should be issued by the state, loss of state assets that exceed what should be received, and reduced revenue from sources of state wealth that should obtain. From the criminal law perspective, corruption is hazardous for society, the nation, and the state. Losses to state finances and the country's economy are real consequences that form the basis for justifying the criminalization of forms of corruption in criminal law policies. This research is normative legal research based on secondary data obtained from legal hierarchies, laws, regulations, and developments in legal issues in Indonesia. The data and information obtained by the authors were analyzed by comparing normative provisions (das sollen) with reality (das sein) that occurs in society. This descriptive and analytical writing provides an overview accompanied by systematic, factual, and accurate explanations. Return of stolen state assets (stolen asset recovery) is critical for developing countries' development because it not only restores state assets but also aims to uphold the rule of law in a society where no one is above the law